A morphometric analysis of intercondylar notch of femur with emphasis on its clinical implications. - Ameet KJ,; Murlimanju BV, (Penerbit UKM, 2014)
The intercondylar notch has been an anatomic site of interest as it lodges the anterior cruciate ligament. The objectives of the present study were to study the morphology and morphometry of femoral intercondylar notch in cadaveric dry bones with emphasis on its clinical implications.The present investigation was performed by using 97 dry femora. The parameters like intercondylar notch width, intercondylar notch depth, condylar width and condylar depth were measured. The shapes of intercondylar notch were also analyzed. The measurements were compared statistically with respect to right and sides and were tabulated. It was observed that the intercondylar notch was having inverted ‘U’ shape morphology in 71 (73.2%) specimens and it was inverted ‘V’ shaped in 26 (26.8%) cases. The mean intercondylar notch width, intercondylar notch depth, condylar width and condylar depth were 11.9 ± 2.7 mm, 26.3 ± 2.4 mm, 72.9 ± 5.3 mm and 57.3 ± 4.3 mm, respectively. It was observed that there was no statistical significance difference observed (p > 0.05) between the right and left sides. The notch width index and notch depth index were determined as 0.25 and 0.46, respectively. The morphometry data of the present study could provide importance to the orthopedicians in prevention and management of knee injuries. We believe that the present study has provided additional information on this subject and these data might be of use to the clinicians who are involved in the diagnosis and management of knee problems.